Arteriovenous malformation as a cause for acute confusion and gastrointestinal bleeding in a primigravida pregnancy. Issue 1 (29th January 2021) - Clarke, Helen; McCormack, Thomas; Paul, Emila; Ford, Jonathan
Abstract : Acute confusion in pregnancy is generally uncommon, given the relatively young and healthy population obstetricians care for. We present an unusual and rare case of acute confusion in a term pregnancy with antecedent history of gastrointestinal (GI) bleeding. A primigravida with no medical history of note, was found to have a haemoglobin of 67 g/L at booking and was commenced on oral iron supplementation. In the third trimester, she presented with haematochezia and had several admissions, requiring 18 units of red blood cells during her pregnancy. At term, she was admitted with acute confusion and GI bleeding, and was subsequently delivered by caesarean section to facilitate ongoing investigation and management of her symptoms. She was diagnosed postnatally with an arteriovenous malformation in the jejunum which required interventional radiology and surgical management for symptom resolution. Her confusion was attributed to hyperammonaemic levels secondary to her high protein load.